Advances in switchable and highly insulating autonomous (self-powered) glazing systems for adaptive low energy buildings. (October 2018) - Ghosh, Aritra; Norton, Brian
Abstract: Building energy reduction requires highly advanced low heat loss, heat gain and comfortable daylight allowing glazing. Presently available glazing systems are classified mainly in two categories, controlling solar heat gain and controlling low heat loss. Low heat loss through glazing systems can be achieved by (i) suppression of convection in the air between the outer panes by use of multiple glass panes or aerogels, (ii) having an inert gas or vacuum between the panes to reduce or eliminate respectively convective heat transfer. In all these systems, low emissivity coatings are also required to reduce the radiative heat transfer. Low heat glazing allows large areas of a building façade to be glazed without large attendant heat losses. However, they require the addition of an ability to switch from transparent to opaque to avoid excessive solar heat gain and to control glare. Electrically actuated electrochromic, liquid crystal and suspended particle device glazing systems and non-electrically-actuated thermochromic, thermotropic, and gasochromic glazing systems offer control of solar heat gain control and daylight. Recent relevant developments are reviewed with the contemporary status of each technology provided. Highlights: Different static and dynamic transparent glazing systems have been evaluated. Electrically actuated switchable EC, SPD and LC glazing systems have been investigated. Combined glazing systems are discussed.